PREVALENCE OF EXTENDED SPECTRUM BETA LACTAMASES AMONG ENTEROBACTERIACEAE AND THEIR ANTIBIOGRAM PATTERN FROM VARIOUS CLINICAL SAMPLES - Segar, Lavanya; Kumar, Shailesh; Kumar, Shailesh; Kumar, Shailesh; Joseph, Noyal Maria; Joseph, Noyal Maria; Sivaraman, Umadevi; Sivaraman, Umadevi; Sivaraman, Umadevi; Joseph, Noyal Maria (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study was attempted to evaluate the prevalence of extended spectrum beta-lactamase (ESBL) among Enterobacteriaceae from different clinical samples from a tertiary care hospital in Puducherry. Methods: Â A total of 204 gram negative isolates from different clinical samples were studied. All isolates were identified, and antimicrobial susceptibility testing was done by standard microbiological procedures. ESBL production was detected by phenotypic confirmatory disc diffusion test (PCDDT).The test was carried according to CLSI guidelines. Results: Out of 204 isolates, 78 (38.2%) tested positive for ESBL production. Klebsiella pneumoniae (50.9%) showed the maximum ESBL positivity. Amikacin, piperacillin- tazobactam and imipenem are the most effective drugs for the treatment of infections caused by ESBL producing organisms. Conclusion: High prevalence of ESBL producing Enterobacteriaceae in hospitals, with a tendency for multi drug resistance, suggests that routine detection is mandatory as this may help in regulating hospital antibiotic policy. Keywords: Extended spectrum beta-lactamase, Phenotypic confirmatory disc diffusion test, antimicrobial resistance, Enterobacteriaceae.